System of Value Drivers for Economic Value Added as the Tools of Integration of the Planning System of an Industrial Enterprise - Кирилл Павлович Васенев (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2017)
An algorithm for integration of planning system has been suggested for an industrial enterprise with the use of project-oriented tactical planning on the basis of value driver system with the top-level ‘economic value added’.